Enhancement of Ca current in the accessory radula closer muscle of Aplysia californica by neuromodulators that potentiate its contractions - Brezina, V (J Neurosci, 1994)
A major goal of neuroscience is to identify the neural and cellular mechanisms of behavior and its plasticity. Progress toward this goal has come particularly from work with a small number of tractable model preparations. One of these is the simple neuromuscular circuit consisting of the accessory radula closer (ARC) muscle of the mollusk Aplysia californica and its innervating motor and modulatory neurons. Contraction of the ARC muscle underlies a component of Aplysia feeding behavior, and plasticity of the behavior is in large part due to modulation of the amplitude and duration of the contractions of the muscle by a variety of modulatory neurotransmitters and peptide cotransmitters, among them the small cardioactive peptides (SCPs), myomodulins (MMs), and serotonin (5-HT). We have studied single dissociated ARC muscle fibers in order to determine whether modulation of membrane ion currents in the muscle might underlie these effects. First, we confirmed that the dissociated fibers were functionally intact: just as with the whole ARC muscle, their contractions were potentiated by 5-HT and SCPB and potentiated as well as depressed by MMA, and their cAMP content was greatly elevated by 5-HT, SCPA and SCPB, and to a lesser extent by MMA and MMB. Next, using voltage-clamp techniques, we found that two ion currents present in the fibers were indeed modulated. The fibers possess a dihydropyridine-sensitive, high- threshold “L”-type Ca current. This current was enhanced by the modulators that potentiate ARC-muscle contractions--5-HT, SCPA and SCPB, and MMA and MMB--but not by buccalinA, a modulator that does not act directly on the ARC muscle. All of the potentiating modulators, as well as elevation of cAMP in the fibers by forskolin or a cAMP analog, maximally enhanced the current about twofold and mutually occluded each other's effects. Since the Ca current supplies Ca2+ necessary for contraction of the muscle, the enhancement of the current is a good candidate to be a major mechanism of the potentiation of the contractions. In the following article we report that the modulators also, to different degrees, activate a distinctive K current and thereby depress the contractions. Net potentiation or depression then depends on the balance between the relative strengths of the modulation of the two ion currents.